StudySmarter AI is coming soon!

- :00Days
- :00Hours
- :00Mins
- 00Seconds

A new era for learning is coming soonSign up for free

Suggested languages for you:

Americas

Europe

Q. 31

Expert-verifiedFound in: Page 772

Book edition
1st

Author(s)
Peter Kohn, Laura Taalman

Pages
1155 pages

ISBN
9781429241861

Use Cartesian coordinates to express the equations for the parabolas determined by the conditions specified in Exercises 22–31.

$r=\frac{\alpha}{1+\mathrm{sin}\theta}$

The equation of the parabola is ${x}^{2}=-2y\alpha +{\alpha}^{2}$.

The given polar equation is $r=\frac{\alpha}{1+\mathrm{sin}\theta}$.

Converting the polar into cartesian co-ordinates,

$r=\frac{\alpha}{1+\mathrm{sin}\theta}\phantom{\rule{0ex}{0ex}}r(1+\mathrm{sin}\theta )=\alpha \phantom{\rule{0ex}{0ex}}r+r\mathrm{sin}\theta =\alpha \phantom{\rule{0ex}{0ex}}\sqrt{{x}^{2}+{y}^{2}}+r\xb7\frac{y}{r}=\alpha \left[\text{since}r=\sqrt{{x}^{2}+{y}^{2}}\text{and}r\mathrm{sin}\theta =y\right]\phantom{\rule{0ex}{0ex}}\sqrt{{x}^{2}+{y}^{2}}+y=\alpha $

On simplifying the equation,

$\sqrt{{x}^{2}+{y}^{2}}+\backslash \mathrm{not}y-\backslash \mathrm{not}y=\alpha -y\phantom{\rule{0ex}{0ex}}\sqrt{{x}^{2}+{y}^{2}}=\alpha -y\phantom{\rule{0ex}{0ex}}{\left(\sqrt{{x}^{2}+{y}^{2}}\right)}^{2}=(\alpha -y{)}^{2}\phantom{\rule{0ex}{0ex}}{x}^{2}+{y}^{2}={\alpha}^{2}+{y}^{2}-2y\alpha \phantom{\rule{0ex}{0ex}}{x}^{2}+{y}^{2}-{y}^{2}={\alpha}^{2}+{y}^{2}-2y\alpha -{y}^{2}\phantom{\rule{0ex}{0ex}}{x}^{2}=-2y\alpha +{\alpha}^{2}$

94% of StudySmarter users get better grades.

Sign up for free